Analysis of Data Privacy Policy, Data Processing Ethics, and Technology Ethics Awareness on User Privacy Protection in West Java - Arief Budi Pratomo; Joko Santoso; Anggun Nugroho; Rully Fildansyah; Arnes Yuli Vandika (West Science Social and Humanities Studies, 2024)
This study investigates the relationships between data privacy policy adherence, data processing ethics, technological ethics awareness, and user privacy protection in West Java, Indonesia. Utilizing a quantitative research design, data was collected through surveys administered to organizations and individual users. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was employed to analyze the data. The results reveal significant positive relationships between data privacy policy adherence, data processing ethics, and technological ethics awareness with user privacy protection. The findings underscore the importance of regulatory compliance, ethical data practices, and user awareness in safeguarding user privacy. These insights provide valuable implications for policymakers, organizations, and users seeking to enhance privacy protection efforts in West Java and beyond.